ANALISIS KEPUASAN MASYARAKAT ATAS KINERJA PEGAWAI PADA KANTOR CAMAT GOMO KABUPATEN NIAS SELATAN - Telaumbanua, Jefri Cantano; Mendrofa, Syah Abadi; Baene, Eduar; Hulu, Fatolosa (FEB Universitas Sam Ratulangi Manado, 2024)
This research aims to determine community satisfaction with employee performance at the Gomo Subdistrict office. This research uses qualitative research with the research sources being the people of Gomo District and employees of the Gomo District Head's office. Qualitative research uses observation, documentation and interviews. Researchers can contribute to designing good research by integrating qualitative methods effectively. The research results show qualitatively that community satisfaction with employee performance at the Gomo Subdistrict office based on indicators of community satisfaction and employee performance can be classified as Satisfactory. This is based on the results of research conducted on community informants receiving services at the Gomo District office who assessed the ability of employees to carry out their duties because employees were unable to understand their duties and provide good service to the community. Keywords: Community Satisfaction, employee Performance